2019
DOI: 10.24869/spsih.2018.457
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal Self-Injury and Identity Development in Adolescents

Abstract: Nesuicidalno samoozljeđivanje (NSSO) je značajan problem mentalnog zdravlja adolescenata. Pretpostavlja se da problemi u formiranju identiteta imaju važnu ulogu u nastanku samoozljeđujućeg ponašanja kod mladih. Ciljevi istraživanja su bili ispitati klinička obilježja u adolescenata s NSSO te istražiti razlike u razvoju identiteta između opće (školske) populacije adolescenata i adolescenata s NSSO. U istraživanju su sudjelovali adolescenti u dobi od 11 do 18 godina oba spola. Kliničku skupinu (n=31) činili su a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Literature showed that lack of identity integration is linked to several maladaptive behaviors, such as non-suicidal self-injury (Ercegović, Paradžik, Maršanić, & Marčinko, 2018;Nakar et al, 2016) and impairments in social functioning due to the inability to reflect on internal mental states of the self and others (De Meulemeester, Lowyck, Vermote, Verhaest, & Luyten, 2017;Penner et al, 2019). In sum, whether identity integration is considered as the healthy outcome of achiving an identity in various identity domains, identity diffusion and its implications are considered the core of PDs and are particularly characteristic of borderline personality organization (Clarkin, Yeomans, & Kernberg, 1999).…”
Section: Pathological Identitymentioning
confidence: 99%
“…Literature showed that lack of identity integration is linked to several maladaptive behaviors, such as non-suicidal self-injury (Ercegović, Paradžik, Maršanić, & Marčinko, 2018;Nakar et al, 2016) and impairments in social functioning due to the inability to reflect on internal mental states of the self and others (De Meulemeester, Lowyck, Vermote, Verhaest, & Luyten, 2017;Penner et al, 2019). In sum, whether identity integration is considered as the healthy outcome of achiving an identity in various identity domains, identity diffusion and its implications are considered the core of PDs and are particularly characteristic of borderline personality organization (Clarkin, Yeomans, & Kernberg, 1999).…”
Section: Pathological Identitymentioning
confidence: 99%
“…Cross-sectional NSSI studies with adolescents in clinical and community settings find positive associations between identity confusion and NSSI, as well as negative associations SELF-CONCEPT AND NONSUICIDAL SELF-INJURY 24 between identity synthesis and NSSI (Brickman, Ammerman, Look, Berman, & McCloskey, 2014;Claes, Luyckx, & Bijttebier, 2014;Claes, Luyckx, Bijttebier, Turner, Ghandi, Smets, …& Hoksbergen, 2015;Ercegović, Paradžik, Boričević Maršanić, & Marčinko, 2018;Gandhi, Claes, Bosmans, Baetens, Wilderjans, Maitra, …& Luyckx, 2016;Luyckx, Gandhi, Bijttebier, & Claes, 2015a;Luyckx, Gandhi, Bijttebier, & Claes, 2015b;Gandhi, Luyckx, Goossens, Maitra, & Claes, 2016;Gandhi, Luyckx, Maitra, Kiekens, & Claes, 2016;Gahndi, Luyckx, Maitra, Kiekens, Verschueren, & Claes, 2017;Gandhi, Luyckx, Adhikari, Parmar, De Sousa, Shah, … & Claes, 2020). These associations remain when controlling for additional factors such as age, gender, anxiety, and depression (Claes et al, 2014;Claes et al, 2015).…”
Section: Self-concept and Nonsuicidal Self-injury 22mentioning
confidence: 99%
“…Two studies to date have examined identity diffusion in NSSI. One study in Croatia examined identity diffusion in a small sample of inpatient adolescents with NSSI and a larger comparison sample of middle-and high-school age adolescents (Ercegović, Paradžik, Boričević Maršanić, & Marčinko, 2018). Inpatient adolescents with NSSI showed heightened identity diffusion relative to the student sample.…”
Section: Self-concept and Nonsuicidal Self-injury 22mentioning
confidence: 99%
“…In addition, given that the 23 LoPF-Q 12-18 identity items were drawn from the AIDA, we also calculated the total diffusion score excluding these overlapping items excluded (“AIDA—no LoPF”). The AIDA has demonstrated reliability and validity in adolescents from a wide range of cultural backgrounds (e.g., Ercegovic et al, 2018; Kassin et al, 2013; Ragelienė & Justickis, 2016; Tardivo et al, 2016) and in an inpatient sample of American adolescents (Lind et al, 2019). In the current study, Cronbach’s alpha indicated high internal consistency in both the healthy control (AIDA: α = .94, AIDA- no LoPF: α = .91) and clinical sample (α = .95, AIDA- no LoPF: α = .95).…”
Section: Methodsmentioning
confidence: 99%